Managing the technological and market uncertainty of composites innovation: a case study of composites manufacturers in Western Canada and interventions by a translational research centre. (17th November 2017) - Fabris, Janna; Roughley, David; Poursartip, Anoush; Maine, Elicia
Abstract: Composites innovation enables new products and processes, but also involves prolonged periods of technological and market uncertainty. Composites manufacturing is dominated by tacit knowledge and the lack of standardization, and thus can be characterized as a low modularity and low maturity technology. Small-to-medium enterprises (SMEs) may lack the resources to undertake research and development (R&D) and may forgo promising advances because of unacceptable levels of technological uncertainty. Where such companies predominate, composites translational research centres (CTRCs), such as the Composites Research Network (CRN) studied here, can play an important role in supporting and developing industrial innovation capabilities. The primary aim of this paper is to ground anecdotal observation to established innovation management theory relating to strategies addressing technological and market uncertainty in science-based technology sectors. To do this, we examine the translation of university-based composites R&D to SMEs. Through detailed case study analysis of two regional SMEs, including interventions by CRN, we examine the technological and market uncertainties encountered by these companies in their commercialization process, and how these uncertainties can be more effectively managed with the translation of composites manufacturing science from university-based labs to SME products. We analyze the current role of CRN in helping SMEs to reduce technological uncertainty, and the potential role of CRN in helping SMEs to identify market opportunity for subsequent innovation. In both instances, we show that CRN's intervention reduced technological risk. The ability to retain manufacturing competencies in Canada and to capitalize on new market opportunities was realized in one of the cases studied. Mistakes made and lessons learned as CRN matured in working with SMEs are discussed. We demonstrate both the uncertainties faced by SMEs in composites innovation and the role a translational research centre can play in managing these uncertainties, highlighting what appears as a key difference between supporting a large company and an SME.